Bioterror deadly invisible weapons - Rudy, Lisa Jo (New York Franklin Watts, 2008)
Learn about bioweapons and the people who fight them with cases drawn from real life
Hurg
5 8
Keywords: Biological warfare; Biological warfare -- Juvenile literature